Bureaucracy and Administration - Ali Farazmand (Taylor and Francis Group, 2009)
Fifteen years have passed since the publication of the fi rst edition of the Handbook of Bureaucracy in 1994. Given that this period has been marked by an intense global movement of antibureaucracy, antigovernment, and antipublic service and administration, the following questions are quite natural: Why do we need another book on bureaucracy now? Does bureaucracy still matter? Th e answer to these challenging questions is that despite this intense negative attitude toward bureaucracy, global interest in the fi rst edition of this book has been overwhelming. Th e book has reached more libraries, university classrooms, and institutional leadership desks than was initially expected. What accounts for such an overwhelming success of the fi rst edition, and the continuing demand for an updated new edition, is itself a remarkable question that all of us in the fi eld of social sciences need to consider, understand, and appreciate. Th e world has become more complex, globalization of corporate capitalism and cultures as well as governance systems has become more rapid and widespread, and the tasks of public governance and administration have become more numerous and demand more institutionally tested solutions and ideas to meet the increasing challenges of the age of hyper-uncertainties. Strategic adaptation to global challenges of the age is an essential task for modern governance, but not all new and untested ideas can off er solutions to complex problems that require established institutional solutions. Bureaucracy is one of those ancient institutions that, despite many negative connotations attached to it, has persisted with durability, dependability, and stabilityâ€”it has been tested for millennia. Despite all innovations and alternative organizational systems, nothing has replaced bureaucracy as the â€œcore of government and large scale corporate governance systems.â€ Bureaucracy has survived millennia of changes, turbulence, and adversarial situations, and it will continue to survive because there is no real replacement for it. Th e overwhelming response to the fi rst volume of this book has been due to the following factors: the need for up-to-date knowledge and information on institutions of government and governance; the interest in what and how things are done elsewhere so comparative knowledge can benefi t from it; the essence of bureaucracy as still the core organization of government; the beauty of an impartially balanced bureaucratic organization as the core institution of governance and administration; and the mere fact that bureaucracy may and can serve as a â€œmothershipâ€ of expertise and a springboard to expand into and cover a wider and broader scope of governance activities and functions with diverse organizational subsystems such as network and collaborative or partnership-based organizational arrangements. Bureaucracy persists because it is instrumental to maintenance, continuity, and enhancement of both capitalist and socialist systems; an instrumental arm of public governance and administration in both its civilian and its military-security forms.